Chronic immune sensory polyradiculopathy (CISP). Issue 1 (5th November 2021) - Ong, Stephanie; Cassidy, Adam
Abstract : Chronic immune sensory polyradiculopathy (CISP) is a rare variant of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). We describe a man with isolated sensory ataxia whose initial investigations included normal nerve conduction studies and normal non-enhanced MR imaging of whole spine, but whose subsequent investigations showed delayed somatosensory evoked potential (SSEP) responses of the lower limbs, elevated cerebrospinal fluid (CSF) protein and lumbosacral nerve roots enhancement on MR imaging. We diagnosed CISP and he improved following intravenous immunoglobulin. Proposed diagnostic criteria for CISP are sensory symptoms with a polyneuropathic distribution without weakness, and normal motor and sensory nerve conduction and electromyography (EMG) studies, plus at least two of: abnormal SSEPs not due to central nervous system (CNS) involvement, MRI showing gadolinium enhancement or hypertrophy of the nerve roots, cauda equina or plexuses, and elevated CSF protein with normal cell count. Intravenous immunoglobulin is an effective treatment.